Kualitas Jaringan E-Learning Berdasarkan Delay - Eka Novvala Dewi; Noveri Lysbetti M (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
During the current pandemic, the education sector uses E-Learning as an online learning medium. One of the famous e-learning is Google Classroom. Because E-Learning is an online learning medium, a test is carried out with calculations using QoS parameters to see its performance and quality. Testing is done on the Wireshark application to see packet delay and uses the THYPON standard. Measurements are made when uploading assignments or subject matter and carried out by three clients for three days. to get the best network quality, the delay measurement results in packets must be less than 150ms. After testing, the third client obtained the best results on the third day, with the lowest delay reaching 9.88ms. At the same time, the highest delay is obtained on the second client on the first day. Therefore, it can be concluded from testing on three clients for three days that the Google Classroom E-learning has a very good network quality with an index of 4 on the TYPHON standard.Keywords: E-Learning, QoS, Delay dan Wireshark.